2017
DOI: 10.1097/j.pain.0000000000001001
|View full text |Cite
|
Sign up to set email alerts
|

Brain signature and functional impact of centralized pain: a multidisciplinary approach to the study of chronic pelvic pain (MAPP) network study

Abstract: Chronic pain is often measured with a severity score that overlooks its spatial distribution across the body. This widespread pain is believed to be a marker of centralization, a central nervous system process that decouples pain perception from nociceptive input. Here, we investigated whether centralization is manifested at the level of the brain using data from 1079 participants in the Multidisciplinary Approach to the Study of Chronic Pelvic Pain Research Network (MAPP) study. Participants with a clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 55 publications
(73 reference statements)
7
100
0
Order By: Relevance
“…Recent advances in brain imaging techniques have allowed for thorough examination of gray matter volume, functional connectivity, and metabolite levels in pain-relevant areas of the brain in chronic pain patients. While brain imaging studies of chronic back pain patients have revealed decreased gray matter in areas involved with pain perception and modulation (Apkarian et al, 2004 ), patients with centralized pain syndromes largely show an increase in gray matter that is associated with greater widespread pain and comorbidity (Schmidt-Wilcke et al, 2007 ; Schweinhardt et al, 2008 ; Seminowicz et al, 2010 ; Kutch et al, 2017a ). Functional connectivity between sensorimotor and insular cortices have largely been reported in chronic urological pain patients, again with an association with pain that is more widespread and lower quality of life scores (Kutch et al, 2015 , 2017b ; Harper et al, 2018 ).…”
Section: Central Sensitizationmentioning
confidence: 99%
“…Recent advances in brain imaging techniques have allowed for thorough examination of gray matter volume, functional connectivity, and metabolite levels in pain-relevant areas of the brain in chronic pain patients. While brain imaging studies of chronic back pain patients have revealed decreased gray matter in areas involved with pain perception and modulation (Apkarian et al, 2004 ), patients with centralized pain syndromes largely show an increase in gray matter that is associated with greater widespread pain and comorbidity (Schmidt-Wilcke et al, 2007 ; Schweinhardt et al, 2008 ; Seminowicz et al, 2010 ; Kutch et al, 2017a ). Functional connectivity between sensorimotor and insular cortices have largely been reported in chronic urological pain patients, again with an association with pain that is more widespread and lower quality of life scores (Kutch et al, 2015 , 2017b ; Harper et al, 2018 ).…”
Section: Central Sensitizationmentioning
confidence: 99%
“…Similar to the aforementioned fMRI study illustrating increased functional connectivity in the emotional-arousal circuit of IBS patients, multiple studies have investigated changes in brain connectivity in patients with IC/PBS. Patients with more widespread pain, affecting multiple and disparate parts of the body outside of the pelvis, had greater increases in gray matter volume and functional connectivity of sensorimotor and insular cortices (Kutch et al, 2017 ). These changes also correlated with decreased physical and mental function.…”
Section: Clinical Evidence Of Early Life Stress-related Visceral Painmentioning
confidence: 99%
“…Patients with a greater number of painful body sites also reported higher pain, anxiety, and depression scores, along with worse quality of life. Changes in functional connectivity between relevant brain structures, as well as increased gray matter, have also been correlated with worsened pain and mental function scores (Kutch et al, 2017 ). These observations support the need for fully phenotyping patients prior to prescribing pharmacological or other interventional treatments.…”
Section: Centralized Pain Phenotypementioning
confidence: 99%
“…Our novel observation of two flare patterns, one with and one without concomitant increases in extrapelvic pain, is consistent with the broader hypothesis of the existence of at least two distinct UCPPS phenotypes. 8,12 Moreover, it also suggests that the pathologies underlying these two phenotypes may contribute to flare pathology. For instance, in participants without COPCs whose localized pain is likely the result of peripheral pathology (eg, peripheral sensitization), increases in pelvic/genital, but not extrapelvic, pain may reflect an exacerbation of peripheral sensitization.…”
Section: Discussionmentioning
confidence: 99%